The national team - shaping the nation`s representation in football - Małczyński, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The national football team represents the nation and speaks for it. The football team plays an important role in the reproduction of national identity and nationalism. It is also used as a tool of public diplomacy. The team is managed by the national football association, which is autonomous from the state authorities. Thanks to its dominant position, the national football association can impose its vision of the representation of the nation. However, the vision of the selector is not received passively. The composition of the national team - an important aspect of the team as a metonymy of the nation - is sometimes contested by the public, especially sports journalists or fans.
Keywords: football; sport; national team; representation; nationalism